Pengaruh Citra Merk Terhadap Keputusan Pembelian Sepeda Motor Honda Di PT. Tunas Dwipa Matra (TDM) Mesuji - Herlina Putri Wulandari; Emy Khikmawati; Sujatmiko Sujatmiko (Universitas Malahayati, 2016)
Motorcycle Competition in the Indonesian automotive market very tight, the motorcyclemanufacturers competing issued their flagship products in order to attract the attention of the market.The point is PT. Tunas Dwipa Matra which one purchase for brand Honda motorcycle in area Mesuji.Purchase for brand Honda motorcycle is decrease of competitive with another dealer in area Mesuji.Detailed of research to do writer in PT. Tunas Dwipa Matra. The method used in this study isobservational methods and statistical data processing. Observation method is done by directobservation, research questionnaires distributed to respondents. While the statistical data processingis to process the data from the respondents' assessment based on the level of perceived and expectedto test the validity, reliability testing, simultaneous test and partial test in to SPSS 15. From theanalysis performance rating of the quality of electric service that gets the highest order of 2,742 is theproduct image, 1,992 is the company image, while the lowest level of -,577 is the user image. Theexplanation research conclusion is variable brand company and variable brand product have toinfluence positive for apart decisions variable, meanwhile variable brand user have to influencenegative for purchasing decisions. Suggestion for PT. Tunas Dwipa Matra (TDM) Mesuji is alwaysimprovement about promotion, because we doing promotion can be increase purchasing decisions bycustomers. Meanwhile for PT. Tunas Dwipa Matra (TDM) Mesuji and brand image Hondamotorcycle, more than famous by people in area Mesuji.